DIMENSIONS OF APPLICATION OF COOPERATIVE SCRIPT METHOD IN SOCIOLOGY LEARNING - Amilah Raden; Nurdin (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2021)
This study aims to determine the dimensions of the application of the cooperative script method in sociology learning. This literature study uses various literature studies to strengthen the research analysis. The data in this literature is obtained from data relevant to the problem to be studied and then other literature studies are carried out such as journals, books, articles, and previous research. This literature study analyzes 30 articles obtained from Google Scholar which are considered relevant by looking at the year the article was published at least the last 10 years. The results of the literature study show that the cooperative script method can change students' skills. This can be seen from the changes that occur in students, namely students' thinking skills, students become critical in speaking/communication, students become critical in writing and students become skilled in listening. In addition, the cooperative script method can also improve student learning outcomes.